Advances in Plant Defense Mechanisms 2022
DOI: 10.5772/intechopen.105942
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress in Millets and Its Response Mechanism

Abstract: Drought is a major abiotic stress that diminishes crop yield and weakens global food security, especially in the current emerging situation of climate change as well as increases in the prevalence and severity of stress elements. Millets are nutrient-dense and capable to resist variety of harsh environmental conditions, including lack of moisture. Millet’s crop has evolved dynamically in terms of morphology, physiology, and biochemically that allow them to flee and/or adapt to adverse environmental situations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Consequently, they effectively utilize the inadequate moisture found in semi-arid areas. 30,31 Millets have a smaller environmental impact than other cereal crop such as paddy and wheat because they frequently require fewer inputs, such as less water, pesticides and fertilizers. 32,33 Research has shown that millet cultivation has a comparatively smaller carbon footprint and water footprint compared to rice and wheat production.…”
Section: Sustainable Production Of Milletmentioning
confidence: 99%
“…Consequently, they effectively utilize the inadequate moisture found in semi-arid areas. 30,31 Millets have a smaller environmental impact than other cereal crop such as paddy and wheat because they frequently require fewer inputs, such as less water, pesticides and fertilizers. 32,33 Research has shown that millet cultivation has a comparatively smaller carbon footprint and water footprint compared to rice and wheat production.…”
Section: Sustainable Production Of Milletmentioning
confidence: 99%
“…Barnyard millet and foxtail millet complete life cycle in 70-80 days, while rice and wheat take about 150-180 days for maturity. Combined with anatomic and physiological adaptations, the dehydration responses allow millets to survive low critical leaf water potential (−1.22 MPa) (Tiwari et al, 2022). The occurrence of stress is evaded by many other traits such as C 4 photosynthetic machinery, fast growth, small leaf area, thickened cell walls, and deep/dense fibrous root system, which maintain water availability and stability during environmental changes (Pardo & VanBuren, 2021).…”
Section: Climate Resiliencementioning
confidence: 99%
“…Wheat, a staple crop, faces reduced yields due to rising temperatures, with estimated losses of 4-16 per cent by 2050 (Tesfaye et al, 2017a). Similarly, millets, which are drought-tolerant crops, are also vulnerable to changing rainfall patterns and increasing temperatures, leading to possible yield reductions of 10-20 per cent (Tiwari et al, 2022). These statistics emphasize the urgent need to implement climate change adaptation strategies and promote climateresilient agricultural practices to safeguard the productivity and sustainability of the major cropping systems in Gujarat, Anand.…”
Section: Introductionmentioning
confidence: 99%